Analisa Sifat Kimia Fisik Fluida dan Perkiraan Temperatur Reservoir Geotermal di Kabupaten Minahasa Selatan - Jeferson Polii; Soenandar Milian Tompunu Tengker (Jurnal Kimia Fullerene, 2022)
The presence of geothermal potential in an area is indicated by the presence of surface manifestations such as hot springs, fumaroles, mud pools, steaming ground, warm ground, geysers, silica deposits, and other manifestations. Chemical and physical analysis of these manifestations can explore the value of subsurface characteristics such as reservoir type, temperature and pressure of reservoir rock formations, as well as the chemical properties of the fluid. The South Minahasa Regency which is the target of the research has geothermal manifestations such as hot springs, steaming ground, silica deposits, and others. The study was conducted to analyze the characteristics of the fluid using geochemical methods and to estimate the temperature of the geothermal reservoir in the manifestation area in South Minahasa Regency. Geothermal manifestation in Pinaesaan village, South Minahasa Regency is a type of chloride fluid. This shows that the geothermal area is a high temperature zone and has a high permeability zone. Geothermal fluid in Pinaesaan village, South Minahasa Regency is in the area of ​​partial equilibrium waters, which indicates that the fluid is not in a state of equilibrium. This is because the fluid has been mixed with surface water. The hot springs in Pinaesaan village are estimated to be an outflow zone from the geothermal system in the area. The estimated temperature of the geothermal reservoir in Pinaesaan Village using a silica quartz geothermometer calculation is 191°C.